A visual dimension of protest: an analysis of interactions during the Russian March - Zuev, D. (Visual Anthropology, 2010)
In this article I analyze the Russian March as a multi-meaning demonstration of political protest. A theoretical perspective of political ritual is used to analyze the structure of the Russian March. The data were collected for the whole period of existence of this March (2005-2008). Data include the visual imagery produced by members and posted on the Internet or published in online newspapers, as well as the results of participant observation on-site during 2007-2008. This case-study of the development of political ritual in post-Soviet Russia helps one to examine the social integrative function of the public holiday and the rituals that it engenders. The Russian March offers a rare window for investigating interaction between activists of a nationalist movement and state authorities. It is one of the few protest rituals to have been repeatedly performed in Russia over the last 5 years.